Anticholinergic Medication Burden in Pediatric Prolonged Critical Illness: A Potentially Modifiable Risk Factor for Delirium. Issue 10 (October 2018) - Madden, Kate; Hussain, Kinza; Tasker, Robert C.
Abstract : Objectives: It is important to describe and understand the prevalence and risk factors for the syndrome of delirium in critical illness. Since anticholinergic medication may contribute to the development of delirium in the PICU, we have sought to quantify anticholinergic medication exposure in patients with prolonged admission. We have used Anticholinergic Drug Scale scores to quantify the magnitude or extent of this burden. Design: Retrospective cohort study, January 2011 to December 2015. Setting: Single academic medical center PICU. Patients: Children under 18 years old with a PICU admission of 15 days or longer, requiring mechanical ventilation. Interventions: None. Measurements and Main Results: Daily Anticholinergic Drug Scale scores for the first 15 days of admission, in each of 88 subjects (total of 1, 320 PICU days), were collected and assessed in relation to demographic data, severity of illness, and medication use. Median (interquartile range) of daily Anticholinergic Drug Scale score was 5 (interquartile range, 3–7). Anticholinergic Drug Scale score was not associated with age, sex, medical history, presenting Severity of Illness score, PICU length of stay, ventilator hours, or hospital mortality. Medications most frequently associated with high Anticholinergic Drug Scale score were low potency anticholinergic drugs such as morphine, midazolam, vancomycin, steroids, and furosemide, with the exception of ranitidine (Anticholinergic Drug Scale score 2). Patients receiving high doses of midazolam infusion had significantly higher Anticholinergic Drug Scale scores compared with those receiving lower or no midazolam dosing. Conclusions: A high number of medications with anticholinergic effects are administered to PICU patients receiving prolonged mechanical ventilation. These exposures are much higher than those reported in adult intensive care patients. Since anticholinergic drug exposure is associated with delirium, further study of this exposure in PICU patients is needed.